2007
DOI: 10.1029/2006jc003982
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ocean models using observed and simulated drifter trajectories: Impact of sea surface height on synthetic profiles for data assimilation

Abstract: [1] The impact of global Navy Layered Ocean Model (NLOM) sea surface height (SSH) on global Navy Coastal Ocean Model (NCOM) nowcasts of ocean currents is investigated in a series of experiments. The studies focus on two primary aspects: the role of NLOM horizontal resolution and the role of differences between the SSH means in NLOM and the Modular Ocean Data Assimilation System (MODAS) climatology. To evaluate the impact of changes to the assimilation system, we compare observed drifter trajectories with traje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 31 publications
5
54
0
Order By: Relevance
“…The papers of Reed et al (1994) and Al-Rabeh et al (2000) showed a qualitative comparison between drifting buoy trajectories and modeled trajectories. In more recent papers, quantitative metrics, based on the separation distance between modeled and observed trajectories, are presented (Price et al, 2006;Barron et al, 2007;Caballero et al, 2008;Sotillo et al, 2008;Huntley et al, 2011;Cucco et al, 2012). A skill score, based on separation distance normalized by the trajectory length, has been recently proposed by Liu and Weisberg (2011).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 1 more Smart Citation
“…The papers of Reed et al (1994) and Al-Rabeh et al (2000) showed a qualitative comparison between drifting buoy trajectories and modeled trajectories. In more recent papers, quantitative metrics, based on the separation distance between modeled and observed trajectories, are presented (Price et al, 2006;Barron et al, 2007;Caballero et al, 2008;Sotillo et al, 2008;Huntley et al, 2011;Cucco et al, 2012). A skill score, based on separation distance normalized by the trajectory length, has been recently proposed by Liu and Weisberg (2011).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Price et al (2006) found that separation distance between modeled and drifters trajectories is 78 km after 3 days, and 229 km after 20 days. RMSE over the integration time, estimated by Barron et al (2007), ranges from 10 to 25 km after 1 day and from 50 to 150 km after 7 days. Caballero et al (2008) showed that after 3 days observed and modeled trajectories separate by 23 km, while after 7 days the separation increases to 46 km.…”
Section: Verification Drifters and Satellite Datamentioning
confidence: 99%
“…The local circulation memory is likely maintained for longer in slowly evolving dynamics, improving the performance of persistence trajectories. Therefore, the ocean model has a tougher persistence benchmark where Lagrangian trajectories are inherently more predictable in the model, that is, in areas of lower square root of the velocity variance (Barron et al, 2007;Özgökmen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…An example of a reasonable choice of M is the commonly used Lagrangian separation distance (Barron et al, 2007;Berta et al, 2015;Castellari et al, 2001;Liu et al, 2014;Phillipson & Toumi, 2017;Rixen & Ferreira-Coelho, 2007;Muscarella et al, 2015), that is, the separation distance between simulated trajectories (computed via an advection scheme) and observed drifters (km):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation